WOMEN STRUGGLE IN 'A MIDSUMMER NIGHT'S DREAM' : DE BEAUVOIR'S FEMINISM PERSPECTIVE - Winarti Winarti; Ana Hening Kusuma (UIN Raden Mas Said Surakarta, 2017)
A Midsummer Night’s Dream is one of Shakespeare’s comedies assumed to be written between 1590- 1597. It can be regarded as one of the comedies because it is full of silly funny things and also has a happy ending although there is seriousness within the work for instance the representation of patriarchal society. This paper aims at describing the women's struggles in the play based on the theory of Simon de Beauvoir regarding the situation of married woman to see the phenomenon found in the work better. As the result of the analysis, it can be concluded that there is a gender awareness which has been presented by Shakespeare in A Midsummer Night’s Dream. He shows that there is gender difference in the play presented by the male and female characters in a restricted patriarchal society of Athens.